Favorable Alleles for Stem Water-Soluble Carbohydrates Identified by Association Analysis Contribute to Grain Weight under Drought Stress Conditions in Wheat - Li, Weiyu; Zhang, Bin; Li, Runzhi; Chang, Xiaoping; Jing, Ruilian (PloS one, 2015)
Drought is a major environmental constraint to crop distribution and productivity. Stem water-soluble carbohydrates (WSC) buffer wheat grain yield against conditions unfavorable for photosynthesis during the grain filling stage. In this study, 262 winter wheat accessions and 209 genome-wide SSR markers were collected and used to undertake association analysis based on a mixed linear model (MLM). The WSC in different internodes at three growth stages and 1000-grain weight (TGW) were investigated under four environmental regimes (well-watered, drought stress during the whole growth period, and two levels of terminal drought stress imposed by chemical desiccation under the well-watered and drought stress during the whole growth period conditions). Under diverse drought stress conditions, WSC in lower internodes showed significant positive correlations with TGW, especially at the flowering stage under well-watered conditions and at grain filling under drought stress. Sixteen novel WSC-favorable alleles were identified, and five of them contributed to significantly higher TGW. In addition, pyramiding WSC favorable alleles was not only effective for obtaining accessions with higher WSC, but also for enhancing TGW under different water regimes. During the past fifty years of wheat breeding, WSC was selected incidentally. The average number of favorable WSC alleles increased from 1.13 in the pre-1960 period to 4.41 in the post-2000 period. The results indicate a high potential for using marker-assisted selection to pyramid WSC favorable alleles in improving WSC and TGW in wheat.